Physical Disability and Labor Market Discrimination: Evidence from a Field Experiment - Charles Bellemare; Marion Gousse; Guy Lacroix; Steeve Marchand (Center for Economic Studies and ifo Institute (CESifo), 2018)
We investigate the determinants and extent of labor market discrimination toward people with physical disabilities using a large scale field experiment. Applications were randomly sent to 1477 private firms advertising open positions. We find that average callback rates of disabled and non-disabled applicants are respectively 14.4% and 7.2%. We find this differential does not result from accessibility constraints related to firm infrastructures. We also find that mentioning eligibility to a government subsidy to cover the cost of workplace adaptation does not increase callback rates. Finally, we estimate that a lower bound of the proportion of discriminating firms is 49.7%.
Keywords: J71; J68; 330; discrimination; disabilities; partial identification